Buyer personas : how to gain insight into your customer's expectations, align your marketing strategies, and win more business - Revella, Adele, ....- (Hoboken, New Jersey : Wiley, 2015)
"See your offering through the buyer's eyes for more effective marketingBuyer Personas is the marketer's actionable guide to learning what your buyer wants and how they make decisions. Written by the world's leading authority on buyer personas, this book provides comprehensive coverage of a compelling new way to conduct buyer studies, plus practical advice on adopting the buyer persona approach to measurably improve marketing outcomes. Readers will learn how to segment their customer base, investigate each customer type, and apply a radically more relevant process of message selection, content creation, and distribution through the channels that earn the buyers' trust. Rather than relying on generic data or guesswork to determine what the buyer wants, the buyer persona approach allows companies to ask the buyer directly and obtain more precise and actionable guidance.Buyer personas are composite pictures of the people who buy solutions, services or products, crafted through a unique type of interview with the people the marketer wants to influence. This book provides step-by-step guidance toward implementing the buyer persona approach, with the advice of an internationally-respected expert. Learn who buys what, and why Understand your buyer's goals and how you can address them Tailor your marketing activities to your buyer's expectations See the purchase through the customer's eyes A recent services industry survey reports that 52 percent of their marketers have buyer personas, and another 28 percent expect to add them within the next two years - but only 14.6 percent know how to use them. To avoid letting such a valuable tool go to waste, access the expert perspective in Buyer Personas, and craft a more relevant marketing strategy"--
Includes bibliographical references (pages199 -201) and index.
Keywords: BUSINESS & ECONOMICS / Consumer Behavior; BUSINESS & ECONOMICS / Marketing / Direct; BUSINESS & ECONOMICS / Marketing / General; Consumer behavior; Marketing -- Management